Solvent-Dependent Synthesis of Perlin Aldehyde from d-Glucal Using Ceric Ammonium Nitrate and TMSCl - Yadav, Yogesh; Tiwari, Amul; Singh, Kavita; Sagar, Ram (Synlett, 2025)
In this study, a solvent-dependent ceric ammonium nitrate (CAN) and TMSCl-mediated synthesis of enantiopure 2,3-dideoxy-α,β-unsaturated carbohydrate enals (Perlin aldehydes) in CH3CN and 1,4-dioxane has been reported. This efficient protocol works well for the various d-glucals (O-acetyl, O-propyl, O-butyl, O-TIPS), and afforded Perlin aldehyde in acceptable to good yields. Thus, in this article we present a quick, efficient, and highly selective method for synthesizing Perlin aldehyde in 1.5 h at 70 °C in good yield.
Keywords: d-glucal; ceric ammonium nitrate; TMSCl; 2-deoxy sugar; Perlin aldehyde